Aussie Current and Myofascial Release in Muscular Power and Muscle: Controlled and Randomized Clinical Trial - Luz1, Ávila Souza; Santos2, Kleyton Trindade; Júnior3, Virgílio Santana; Santos1, Lucas Freitas; Rodrigues1, ara Lourdes Moreno; Brito, Diego Correia; Evangelista, Carlos Machado Ataíde; Sousa, Lázaro Silva; Malaquias, Dado Guilyos Santos; Gomes, Mariana Meira; Meira, Winnie da Conceição; Sampaio, Lucas Silveira (International Journal of Advanced Engineering Research and Science, 2019)
Among the techniques identified as the possibility of accelerating and/or optimizing the process of muscle, strength gain is myofascial release and electrostimulation. Given this context, this study seeks to analyze and compare the effects of combined use of the Aussie current and myofascial release on muscle strengthening. This is a cross-sectional study, analytical and descriptive, experimental, comparative, controlled and randomized. The study sample is non-probabilistic composed of 16 volunteers who will be subdivided into four groups. The muscular strength gain of the quadriceps muscles will be evaluated bilaterally through the countermovement vertical jump. The interferential statistics used were through the paired Student t-test to verify the difference between the means before and after the treatments in each group, and it was also the Mannn-Whitney U test to verify the differences concerning the techniques. The significance level adopted will be 5% (α = 0.05). Regarding the parameters of the evolution of muscular strength gain related to vertical jump distance, significant statistical differences were observed only for GL and GT in the initial-intermediate evaluation (p = 0.025 and p = 0.035, respectively). Regarding the evolution parameters of mean differences of 70% of the maximum load of 1RM, significant statistical differences were observed only for GA in the initial-intermediate and intermediate-final evaluations (p = 0.035 p = 0.035, respectively). It was not possible to identify a statistically significant advantage of the combined use of the techniques in the Todos Group over their isolated use.